Marketing Communication in the Commercial and Business Development Division of PT Len Industri Cooperative - Raisha Shahana; Detya Wiryany; Zikri Fachrul Nurhadi (Information Technology and Science (ITScience), 2026)
Marketing communication is a form of communication aimed at introducing, establishing, and creating interactions between companies and their business partners and consumers. This study aims to analyze the implementation of marketing communications carried out by the Commercial and Business Development Division at the Employee Cooperative of PT. Len Industri based on the Integrated Marketing Communication (IMC) approach. This study uses a descriptive qualitative approach, where data is obtained through direct observation and interviews with relevant parties, as well as a review of supporting documents in the form of digital marketing content and business activity reports. The results of the study show that marketing communication activities are carried out through the integrated use of digital and conventional media, including the use of social media, direct delivery of information to cooperative members, and the use of promotional media placed within the company environment. The success of these marketing communication activities is supported by the availability of various internal communication channels, the proximity of the communication targets, the majority of whom are employees of PT. Len Industri, and the existence of business units that continuously generate promotional activities. However, obstacles were also found, such as limited content production tools, a lack of resources focused on marketing, and a lack of consistency in messaging across communication channels.